DEVELOPMENT OF MODERN MARKETING IN UZBEKISTAN - Usmonova Adiba Azimovna; Eshqobilova Nargiza Mengnorovna (American Journals Publishing, 2023)
This article describes the essence of the concept of marketing, the history of the marketing and modern marketing. It is also mentioned on the management of marketing, about the concept of marketing.
Keywords: marketing, marketing development, marketing concept, modern marketing